A modern view of the psychosomatic consequences of the COVID-19 pandemic - Omelyanovich, Vitalii; Мішиєв, Вячеслав; Михайлов, Борис; Гриневич, Євгенія; Кузнецов, Ігор (Psychosomatic Medicine and General Practice, 2023)
This text is the thesis of the VI scientific and practical conference with international participation "Psychosomatic medicine: science and practice". Which will take place on November 2-3, 2023 in the city of Kyiv.